ANALYSIS OF STUDENTS' DIFFICULTIES IN SOLVING ALGEBRA PROBLEMS AND ITS IMPLICATIONS FOR UNDERSTANDING MATRIXES - atin risnawati; Muhammad Permadi (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study aims to analyze the challenges faced by students in solving algebra problems and how these challenges affect their understanding of matrix material. The study was conducted at IAIN Kerinci using a qualitative case study approach. Data were collected through evaluation and interviews with three students who were selected purposively based on the level of difficulty shown in solving algebra problems. The results of the study indicate that difficulties in algebra, especially in basic operations, factoring, and elimination and substitution methods, have a direct impact on students' understanding in solving matrix problems. There are differences in ability between students who are strong in algebra but weak in matrices, and vice versa. Difficulty in transferring knowledge from algebra to the matrix context is also a major obstacle. This study provides important implications for learning design, namely the need for explicit integration between algebra and matrix concepts through contextual and participatory learning models